1999
DOI: 10.1385/abab:78:1-3:547
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production Using Concentrated Oak Wood Hydrolysates and Methods to Detoxify

Abstract: Ethanol production from concentrated oak wood hydrolysate was carried out to obtain a high ethanol concentration and a high ethanol yield. The effect of added inhibitory compounds, which are typically produced in the pretreatment step of steam-explosion on ethanol fermentation, was also examined. p-Hydroxybenzoic aldehyde, a lignin-degradation product, was the most inhibitory compound tested in this study. Compounds with additional methyl groups had reduced toxicity and the aromatic acids were less toxic than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 23 publications
0
21
1
7
Order By: Relevance
“…However, for those treated with low-temperature sterilization (85°C), only a slight increase of total phenolics (less than 8% compared to 33.7% from normal sterilization groups) and a decrease in pH were observed except for samples detoxiWed by overliming, which exhibited decreased total phenolics. These results indicate that low-temperature sterilization, when compared to normal autoclaving, prevented the release of additional phenolic compounds and other acidic inhibitors from soluble lignin [15]. The combination of overliming and low-temperature sterilization resulted in a 65% removal of total phenolics from the original membrane-treated wood hydrolysate.…”
Section: Resultsmentioning
confidence: 84%
“…However, for those treated with low-temperature sterilization (85°C), only a slight increase of total phenolics (less than 8% compared to 33.7% from normal sterilization groups) and a decrease in pH were observed except for samples detoxiWed by overliming, which exhibited decreased total phenolics. These results indicate that low-temperature sterilization, when compared to normal autoclaving, prevented the release of additional phenolic compounds and other acidic inhibitors from soluble lignin [15]. The combination of overliming and low-temperature sterilization resulted in a 65% removal of total phenolics from the original membrane-treated wood hydrolysate.…”
Section: Resultsmentioning
confidence: 84%
“…In this paper, the discussions on the phenolic compounds were based on the removal of ferulic acid and syringaldehyde, some of the compounds found at higher concentrations in hemicellulose hydrolysates [10,28]. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a better understanding of the aforementioned inhibitors and how to mitigate their negative effects is crucial [8]. For cellulosic ethanol production, the effects of the inhibitors formed during acid hydrolysis of biomass on the growth of Saccharomyces cerevisiae and ethanol production have been well investigated [8][9][10][11]. It was found that S. cerevisiae can survive at external pH higher than 4.5 and maximum concentration of undissociated acetic acid of \5 g/L [12].…”
Section: Introductionmentioning
confidence: 99%